2018
DOI: 10.1007/s10529-018-2624-2
|View full text |Cite
|
Sign up to set email alerts
|

Application of microbial fuel cell technology for vinasse treatment and bioelectricity generation

Abstract: Objective Our study evaluated the performance of different two-chambered microbial fuel cell (MFC) prototypes, operated with variable distance between electrodes and Nafion membrane and specific inoculum concentration, applied for vinasse treatment. Results The performance of the developed MFC resulted in a maximum current density of 1200 mA m-2 and power density of 800 mW m-2 in a period of 61 days. MFC performed a chemical oxygen demand removal at a rate ranging from 51 to 60%. Conclusions Taking our prelimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Mevastatin removal through traditional wastewater treatment methods was reported to be as low as 34%. 46 Our results suggest that significant amount of mevastatin up to 95% could be removed in MECs. Since the type of substrates used as the carbon source in MECs significantly affect the bioactivity and hydrogen generation performance, 47 the removal and biodegradation of toxic pharmaceuticals including mevastatin could be enhanced using optimized substrates in future.…”
Section: Resultsmentioning
confidence: 62%
“…Mevastatin removal through traditional wastewater treatment methods was reported to be as low as 34%. 46 Our results suggest that significant amount of mevastatin up to 95% could be removed in MECs. Since the type of substrates used as the carbon source in MECs significantly affect the bioactivity and hydrogen generation performance, 47 the removal and biodegradation of toxic pharmaceuticals including mevastatin could be enhanced using optimized substrates in future.…”
Section: Resultsmentioning
confidence: 62%
“…It was reported that 60-70% of clofibric acid and more than 75% of bezafibrate and gemfibrozil were removed [31]. Due to its recalcitrant nature, however, mevastatin elimination via conventional wastewater treatment was reported to be as low as 34% [32]. Using MFCs, however, we were able to demonstrate almost complete removal of mevastatin.…”
Section: Resultsmentioning
confidence: 69%
“…Among the several substrates, wastewater is a resource-rich medium that MFCs may handle. Several reports have been published on the direct generation of electricity from complex organic wastewater, including municipal, swine wastewater, dairy wastewater, slaughterhouse wastewater, rice mill wastewater, tannery wastewater, cassava mill wastewater, molasses wastewater, refinery wastewater, brewery wastewater, winery wastewater, chemical wastewater, sulfide-rich wastewater, landfill leachate, food waste leachate, azo dye, and solid substrates such as rice straw [ 49 , 50 , 51 , 52 ]. MFCs can also simultaneously remove sulfide and nitrate from synthetic wastewater and sulfate–sulfide-rich wastewaters [ 53 ].…”
Section: Factors Affecting the Performance Of An Mfcmentioning
confidence: 99%